(untitled) (Strathmore Law Review, 2025)
Land is an unparalleled cornerstone of our identity, cultural heritage, and spiritual resonance and has often dictated the pulse of nationhood. The Constitution of Kenya stands as the supreme arbiter on land matters, rendering all other laws inconsistent with it null and void to the extent of their inconsistency. Article 40 thereunder enshrines property rights, a fundamental human entitlement. However, enforcing these rights fully pivots on the acquisition of a definite title through a successful legal registration process. The land registration system aims to provide secure titles through streamlined registration processes and indefeasible ownership, guaranteeing transparency and preventing fraud. This article critiques the Supreme Court’s decision in the Dina Management case on the conclusiveness of search and the doctrine of a bona fide purchaser. This paper posits that the Dina management precedent narrowly interprets Article 40, thereby imposing undue burdens on bona fide purchasers, who are made to bear the brunt of historical land injustices and flawed registry practices under the guise of the sanctity of titles. This article concludes by proposing impactful legal and administrative solutions to strengthen this cornerstone of property law and crucial human rights in Kenya, ensuring landowners enjoy a robust and secure legal framework.